Price Leadership and Dynamic Aspects of Oligopoly in U.S. Manufacturing - Gisser, Micha (Journal of Political Economy, 1984)
This study, which covers a sample of 314 four-digit industries taken from an exhaustive set of 450 four-digit industries, shows that increases in concentration associated with rising productivity occur mainly in low-concentration industries, while decreases in concentration associated with rising productivity occur mainly in high concentration industries. The empirical results of this study indirectly lend support to a plausible hypothesis that a small group of firms makes a big impact on the productivity of an initially unconcentrated industry and thereby concentrates it. Later, the small firms imitate the now big firms, and concentration goes down while productivity keeps rising.